A pilot study on early microgliogenesis following unilateral vestibular neurectomy: A key player in vestibular compensation? - Jessica Trico; Emna Marouane; Alain Tonetto; Isabelle Watabe; Agnes Lapotre; Brahim Tighilet (PLoS ONE, 2026)
Following unilateral vestibular damage, several behavioral deficits arise, referred to as vestibular syndrome. At the central level the vestibular syndrome is associated with an imbalance in neuronal activity between the two vestibular nuclei (VN). Its recovery is correlated with a rebalancing of the electrophysiological activity between both VN, known as vestibular compensation. Key plasticity mechanisms within the VN involved in this mechanism include, among others, neurogliogenesis, modulation of neuronal excitability and increased histamine release. In this study, we aimed to characterize the acute glial cell differentiation lineage in response to unilateral vestibular neurectomy (UVN) in the deafferented VN. We further assessed whether this response is influenced by the histaminergic system. To achieve this, betahistine dihydrochloride (BD), was used to stimulate histamine synthesis and release in the VN. After UVN, 2 animal groups were treated orally during 3 days with either BD treatment (UVN BD group, 50 mg/kg/day) or placebo (UVN placebo group). We present preliminary evidence of acute and abundant microgliogenesis restricted to the deafferented VN in both groups. This phenomenon does not appear to be mediated by BD treatment but may reflect an intrinsic biological adaptative mechanism. Further investigations, including Sholl analysis, would be essential to characterize microglia, which may represent a key player in vestibular compensation.